Delineation of Criteria for Admission to Step down in the Mild Traumatic Brain Injury Patient. Issue 1 (January 2016) - Bardes, James M.; Turner, Jason; Bonasso, Patrick; Hobbs, Gerald; Wilson, Alison
Patients that suffer a mild traumatic brain injury (TBI) with intracranial hemorrhage are commonly admitted to an intensive care unit with repeat imaging in 12 to 24 hours. This is costly to the health-care system. This study aimed to evaluate this practice and to identify criteria to triage patients to lower levels of monitored care. A retrospective review was performed at a university-based Level I trauma center. Patients with mild TBI were included. Data were collected on demographics, neurological status at 6, 12, and 24 hours, CT scan results, and medical or surgical interventions were required. A total of 389 patients were evaluated, 53 had a documented neurological decline while being admitted. Factors found to be associated with a neurological decline included Glasgow Coma Scale (GCS) < 15 ( P = 0.002), age greater than 55 ( P < 0.001), and warfarin use ( P = 0.039). Aspirin and Plavix were not associated with neurological decline. No patient age <55 with a GCS of 15 had a documented decline. Several risk factors were found to be associated with neurological decline after mild TBI. These include age, GCS < 15, and warfarin use. Patients aged <55 with GCS 15, posed minimal risk for deterioration. Patients aged <55 and with a GCS of 15 can be admitted to a monitored step-down bed with less frequent neurological checks.